Optimal. Leaf size=27 \[ 4 \left (5+e^{\frac {2 \left (-3-e^{4-2 x}+x\right )}{x}}\right )-x \]
________________________________________________________________________________________
Rubi [F] time = 1.67, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {e^{-2 x} \left (-e^{2 x} x^2+\exp \left (\frac {2 e^{-2 x} \left (-e^4+e^{2 x} (-3+x)\right )}{x}\right ) \left (24 e^{2 x}+e^4 (8+16 x)\right )\right )}{x^2} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \left (-1+\frac {8 e^{-\frac {2 \left (3+e^{4-2 x}-x+x^2\right )}{x}} \left (3 e^{2 x}+e^4 (1+2 x)\right )}{x^2}\right ) \, dx\\ &=-x+8 \int \frac {e^{-\frac {2 \left (3+e^{4-2 x}-x+x^2\right )}{x}} \left (3 e^{2 x}+e^4 (1+2 x)\right )}{x^2} \, dx\\ &=-x+8 \int \left (\frac {3 e^{2 x-\frac {2 \left (3+e^{4-2 x}-x+x^2\right )}{x}}}{x^2}+\frac {e^{4-\frac {2 \left (3+e^{4-2 x}-x+x^2\right )}{x}} (1+2 x)}{x^2}\right ) \, dx\\ &=-x+8 \int \frac {e^{4-\frac {2 \left (3+e^{4-2 x}-x+x^2\right )}{x}} (1+2 x)}{x^2} \, dx+24 \int \frac {e^{2 x-\frac {2 \left (3+e^{4-2 x}-x+x^2\right )}{x}}}{x^2} \, dx\\ &=-x+8 \int \left (\frac {e^{4-\frac {2 \left (3+e^{4-2 x}-x+x^2\right )}{x}}}{x^2}+\frac {2 e^{4-\frac {2 \left (3+e^{4-2 x}-x+x^2\right )}{x}}}{x}\right ) \, dx+24 \int \frac {e^{\frac {2 \left (-3-e^{4-2 x}+x\right )}{x}}}{x^2} \, dx\\ &=-x+8 \int \frac {e^{4-\frac {2 \left (3+e^{4-2 x}-x+x^2\right )}{x}}}{x^2} \, dx+16 \int \frac {e^{4-\frac {2 \left (3+e^{4-2 x}-x+x^2\right )}{x}}}{x} \, dx+24 \int \frac {e^{\frac {2 \left (-3-e^{4-2 x}+x\right )}{x}}}{x^2} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.50, size = 27, normalized size = 1.00 \begin {gather*} 4 e^{2-\frac {6}{x}-\frac {2 e^{4-2 x}}{x}}-x \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.66, size = 29, normalized size = 1.07 \begin {gather*} -x + 4 \, e^{\left (\frac {2 \, {\left ({\left (x - 3\right )} e^{\left (2 \, x\right )} - e^{4}\right )} e^{\left (-2 \, x\right )}}{x}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.27, size = 23, normalized size = 0.85 \begin {gather*} -x + 4 \, e^{\left (\frac {2 \, {\left (x - e^{\left (-2 \, x + 4\right )} - 3\right )}}{x}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.22, size = 33, normalized size = 1.22
method | result | size |
risch | \(4 \,{\mathrm e}^{-\frac {2 \left (-x \,{\mathrm e}^{2 x}+{\mathrm e}^{4}+3 \,{\mathrm e}^{2 x}\right ) {\mathrm e}^{-2 x}}{x}}-x\) | \(33\) |
norman | \(\frac {\left (-{\mathrm e}^{2 x} x^{2}+4 x \,{\mathrm e}^{2 x} {\mathrm e}^{\frac {2 \left (\left (x -3\right ) {\mathrm e}^{2 x}-{\mathrm e}^{4}\right ) {\mathrm e}^{-2 x}}{x}}\right ) {\mathrm e}^{-2 x}}{x}\) | \(54\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.61, size = 25, normalized size = 0.93 \begin {gather*} -x + 4 \, e^{\left (-\frac {2 \, e^{\left (-2 \, x + 4\right )}}{x} - \frac {6}{x} + 2\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 3.64, size = 26, normalized size = 0.96 \begin {gather*} 4\,{\mathrm {e}}^{-\frac {2\,{\mathrm {e}}^{-2\,x}\,{\mathrm {e}}^4}{x}}\,{\mathrm {e}}^2\,{\mathrm {e}}^{-\frac {6}{x}}-x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.26, size = 26, normalized size = 0.96 \begin {gather*} - x + 4 e^{\frac {2 \left (\left (x - 3\right ) e^{2 x} - e^{4}\right ) e^{- 2 x}}{x}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________